2013
DOI: 10.1007/s11033-013-2700-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interleukin gene polymorphisms on development of acute pancreatitis: a systematic review and meta-analysis

Abstract: Several epidemiological studies have assessed the associations of interleukin (IL) gene polymorphisms with acute pancreatitis (AP) in different populations. However, the results were inconclusive. Therefore, we performed the present study to comprehensively evaluate the associations of IL gene polymorphisms and susceptibility to AP. Systematic searches of the PubMed, Web of Science, Embase, CNKI, CBMdisc and Google Scholar until February 27, 2013, as well as hand searching of the references of identified artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…In recent years, several studies have reported the association between gene polymorphisms and risk of acute pancreatitis (Ozhan et al, 2010;Yin et al, 2012Yin et al, , 2013. In this study, we found that IL-8 -251T/A polymorphisms were associated with risk of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 52%
“…In recent years, several studies have reported the association between gene polymorphisms and risk of acute pancreatitis (Ozhan et al, 2010;Yin et al, 2012Yin et al, , 2013. In this study, we found that IL-8 -251T/A polymorphisms were associated with risk of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 52%
“…However, the detailed etiology underlying AP remains unclear. Previous studies showed that inflammatory cytokines are important risk factors of AP (Gu et al, 2013;Yin et al, 2013;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…However, whether polymorphisms of inflammatory cytokines are associated with risk of AP is unknown. Few studies have investigated the association between interleukin gene polymorphism and AP (Chen et al, 2009;Yin et al, 2013). Therefore, we investigated the association between polymorphisms of 2 main proinflammatory cytokines (IL-1b and IL-6) and the risk of AP.…”
Section: Introductionmentioning
confidence: 99%